2009
DOI: 10.1098/rspb.2009.0498
|View full text |Cite
|
Sign up to set email alerts
|

A chemical signal of offspring quality affects maternal care in a social insect

Abstract: Begging signals of offspring are condition-dependent cues that are usually predicted to display information about the short-term need (i.e. hunger) to which parents respond by allocating more food. However, recent models and experiments have revealed that parents, depending on the species and context, may respond to signals of quality (i.e. offspring reproductive value) rather than need. Despite the critical importance of this distinction for life history and conflict resolution theory, there is still limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 42 publications
2
69
0
Order By: Relevance
“…On a proximate level, the transgenerational effects of maternal loss on nymph defence could be mediated by a parent-of-origin effect on the offspring's chemical signatures. These signatures are known to mediate behavioural interactions between earwig mothers and nymphs as well as among nymphs, to be flexible over time, and to determine the amount of food provisioned by mothers [38].…”
Section: Discussionmentioning
confidence: 99%
“…On a proximate level, the transgenerational effects of maternal loss on nymph defence could be mediated by a parent-of-origin effect on the offspring's chemical signatures. These signatures are known to mediate behavioural interactions between earwig mothers and nymphs as well as among nymphs, to be flexible over time, and to determine the amount of food provisioned by mothers [38].…”
Section: Discussionmentioning
confidence: 99%
“…The developmental time for first clutch nymphs was estimated by counting the number of days from hatching to the first observation of a second instars nymph in a clutch, a good measure of mean developmental time of the entire brood [22]. Finally, food provisioning towards first clutch nymphs was estimated using four successive steps that started at day 5 and consisted in (i) food depriving mothers and nymphs for 24 h, (ii) isolating females for 1 h while offering them green-coloured food, (iii) putting each female back in contact with 20 of its foster nymphs for 15 h, and (iv) calculating the proportion of nymphs with green gut [22,27]. The actual number of nymphs tended by foster mothers was not significantly correlated with our measure of food provisioning to the 20 nymphs (Pearson correlation test, r ¼ 20.053, p ¼ 0.51).…”
Section: Methodsmentioning
confidence: 99%
“…Husbandry conditions and general handling up to the hatching of clutches followed the protocols described in detail by Kölliker (2007) and Mas et al (2009). For logistic reasons, that is, to spread out egg-laying and hatching, we split the lab population in two sub-populations that were set up either in July or October under a short-day photoperiod regime to trigger egg-laying (photoperiod/temperature: 8:16h / 20:15°C (day-night) and 50% relative humidity).…”
Section: Husbandrymentioning
confidence: 99%
“…Most of these studies manipulated the short-term nutritional condition (hunger) of offspring and, hence, tested shortterm, potentially transient, effects of offspring signals on the amount of food provisioned by parents. Fewer studies, particularly on colouration and UV-reflectance in birds (Lyon et al 1994;Price and Ydenberg 1995;Saino et al 2000;Bize et al 2006;Tanner and Richner 2008) and recently on a chemical signal in an insect (Mas et al 2009), also showed that condition-dependent signals not always function as signals of short-term "need" but sometimes reflect a longer-term nutritional effect as an offspring signal of "quality" or reproductive value. Thus, offspring signals may contain a range of information influencing parental investment in terms of the amount and/or maintenance and duration of care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation